Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Sikap Remaja Putri tentang Anemia di SMKN 1 Sitiung, Dharmasraya - noviasafitri; Putri, Astuti Ardi; Putri , Dian Eka (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2025)
According to the World Health Organization (WHO) 2021, research data conducted in 2020 increased the number of anemia cases from 1.42 billion to 1.74 billion. Based on the data collected, it shows that 18 out of 42 girls suffering from anemia in SMKN 1 Sitiung in 2022 will increase to 34 out of 58 girls in 2023. The aim of this research is to determine the effect of health education on girls' knowledge and attitudes about anemia at SMKN 1 Sitiung in 2024. This research is pre-experimental research using a design (one group pre test) with a population of 39 34 people and the Whole Sampling method. Based on univariate analysis, it was obtained that low pre-test recognition was 29, namely 85.3%, and good post-test recognition was 34, namely 100%, and the post-test was 23 negatives. That is, 67.6 percent, and after being tested, the majority was 29. After learning about anemia in young women, their attitude was positive. Paired results using the Wilcoxon test and data processing using the SPSS program. The results of research on the influence of health education on adolescents' knowledge and attitudes towards anemia show that the knowledge and attitude value is P = 0.000 because the P value is ≤ 0.05. It can be concluded that health education influences teenagers' knowledge and attitudes about anemia. The teachers' council is advised to actively monitor the consumption of iron tablets and support education related to anemia to improve the health of female students.